(untitled) (Research, Society and Development, 2020)
In the Brazilian context, Vocational and Technological Education (EFA) is historically marked by the duality between technical education, which prepares students for manual work and for the less favored segments, and scientific education, which includes quality and intellectual education. for a small fragment of society. However, it can be seen that over time there is an intense movement for an education based on the integral development of the individual that prepares him not only for professional insertion, but with human emancipation as a horizon. From this perspective, the objective of this study was to conduct a survey of the number of graduating students and graduates from 2012 to 2017 in the technical courses of Medium Level, Integrated mode, Environment, Electrical and Buildings, offered in a Federal Public institution of technological base. Based on the information obtained, it was found that the rate of graduating students, who only met the requirements for obtaining a high school diploma, ranged from 6% to 73%, and that of graduated students, who met the requirements. to obtain certification for immediate insertion in the labor market, ranged from 27% to 94%. The data obtained allow us to infer that the training provided by the institution not only includes the technical skills required by the market, but also enables the access to scientific knowledge and the development of behaviors that allow the choice for immediate entry into the labor market or the continuing education.